Transferability, mobility and youth training in Germany and Britain: A simple theoretical analysis - Clark, Damon; Fahr, Rene (KONJUNKTURPOLITIK-BERLIN-)

Der Einfluss elektronischer Medien auf Geschäftsbeziehungen: Eine empirische Studie am Beispiel des Electronic Banking - Eggert, Andreas (Marketing ZFP)

Customer perceived value: a substitute for satisfaction in business markets? - Eggert, Andreas; Ulaga, Wolfgang (Journal of Business & Industrial Marketing)

Proceedings of the 10th International Colloquium in Relationship Marketing.

eCRM – Electronic Customer Relationship Manage¬ment: Management der Kundenbeziehungen im Internet-Zeitalter.

Offene webbasierte Lernumgebungen - E-Learning in der beruflichen Rehabilitation

Concurrency and Loose Semantics of Open Graph Transformation Systems - Heckel, Reiko; Llabrés, Mercé; Ehrig, Hartmut; Orejas, Fernando (Mathematical Structures in Computer Science)

Consistent Interaction of Software Components - Engels, Gregor; Küster, Jochen; Groenewegen, Luuk (Transactions of the SDPS: Journal of Integrated Design & Process Science)
Constructing complex software systems by integrating different software components is a promising and challenging approach. With the functionality of software components given by models it is possible to ensure consistency of such models before implementation in order to successfully build the system. Models consisting of different submodels, the absence of an overall formal semantics and the numerous possibilities of employing models requires the development of techniques ensuring the consistency. In this paper, we discuss the issue of consistency of models made up of different submodels proposing a concept for the management of consistency. Consistency management relies on a consistency concept and a process for ensuring consistency of models. We introduce a consistency concept for software components modeled in the Unified Modeling Language (UML) and devise suitable consistency checks. On this basis, we propose a process how to locate and resolve inconsistencies, thus ensuring the consistency of models and by that the consistency of componentbased systems derived from those models.

Formal Agent-Oriented Modeling with Graph Transformation - Depke, Ralph; Heckel, Reiko; Küster, Jochen (Science of Computer Programming)

MuSofT - Multimedia in der Softwaretechnik - Doberkat, Ernst-Erich; Engels, Gregor (Informatik Forschung und Entwicklung)
Im BMBF-Verbundprojekt MuSofT werden multimediale Lehrmaterialien für die Lehre der Softwaretechnik entwickelt. Neben den inhaltliche Aspekten sind die Distribution und die Lizenzierung der erstellten Lehrmaterialien wichtige Themakomplexe, um die Nachhaltigkeit des Projektes zu erhöhen. In diesem Papier stellen wir die in MuSofT gewählten Lösungen einer Open-Content-Lizenz sowie eines Portals zur Distribution der entwickelten Materialien vor.

Compositional SOS and Beyond: A Coalgebraic View of Open Systems - Corradini, Andrea; Heckel, Reiko; Montanari, Ugo (Theoretical Computer Science)

Lernfeldkonzeption und schulisches Wissensmanagement - Dilger, B.; Kremer, H.-Hugo (Bildungsmanagement im Lernfeldkonzept - curriculare und organisatorische Gestaltung)

Neues Lernen in vernetzten Lernumgebungen - Gramlinger, F.; Kremer, H.-Hugo (Perspektiven der kaufmännischen Berufsbildung. Entwicklungen im Spannungsfeld globalen Denkens und lokalen Handelns)

Nachwuchsgewinnung unter Beachtung des Medienverhaltens von Jugendlichen - Kremer, H.-Hugo (Handwerk Magazin)

Medienverhalten von Jugendlichen - Neue Anforderungen und Potenziale für Lehren und Lernen - Dilger, B.; Hertle, E.-M.; Kremer, H.-Hugo (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Offene webbasierte Lernumgebungen. Zur Notwendigkeit vernetzter Lehr- und Lernumgebungen - Kremer, H.-Hugo (bwp@ Ausgabe Nr. 2)

Virtuelle Wissensforen. Konsequenzen für Forschung und Entwicklung - Kremer, H.-Hugo (bwp@ Ausgabe Nr. 2a (Sonderheft))

Editorial 'Forschung in-mit-durch webbasierte Lernumgebungen' - Gramlinger, F.; Kremer, H.-Hugo (bwp@ Ausgabe Nr. 2a (Sonderheft))

Wissensforen als Keimzelle des Wissensmanagements in der dualen Ausbildung - Fallbeispiel aus dem Modellversuch WisLok - Dilger, B.; Kremer, H.-Hugo (Berufsbildung)

Offene webbasierte Lernumgebung - Annäherung und Differenzierung - Kremer, H.-Hugo (Offene webbasierte Lernumgebung - E-Learning in der beruflichen Rehabilitation)

Variante 2: Wissensforum - Kremer, H.-Hugo (Offene webbasierte Lernumgebung - E-Learning in der beruflichen Rehabilitation)

Neue Lernkonzepte in/mit dem Internet - Gramlinger, F.; Kremer, H.-Hugo (Offene webbasierte Lernumgebung - E-Learning in der beruflichen Rehabilitation)

Wissensmanagement - ein Weg zur Professionalisierung berufsbildender Schulen - Dilger, B.; Kremer, H.-Hugo (Regionale Netzwerke - ohne berufliche Schulen nicht möglich)

Gestaltung eines standortspezifischen Wissensforums - Entwicklungsbericht aus dem Modellversuch WisLok - Hertle, E.-M.; Kremer, H.-Hugo (Kölner Zeitschrift für Wirtschaft und Pädagogik Online)

Wissensforen, (k)ein Allheilmittel für Lernortkooperation? - Erfahrungen aus dem Modellversuch WisLok - Dilger, B.; Hertle, E.-M.; Kremer, H.-Hugo (Berufs- und Wirtschaftspädagogik Online)

Kundenbeziehungsmanagement für elektronische Dienstleistungen - Fassott, G; Eggert, A (Jahrbuch Dienstleistungsmanagement 2002: Electronic Services)

High-Level Net Processes - Ehrig, Hartmut; Hoffmann, Kathrin; Padberg, Julia; Baldan, Paolo; Heckel, Reiko (Formal and Natural Computing: Essays Dedicated to Grzegorz Rozenberg)

Towards Team-Automata-Driven Object-Oriented Collaborative Work - Engels, Gregor; Groenewegen, Luuk (Formal and Natural Computing: Essays Dedicated to Grzegorz Rozenberg)
The paper studies and compares two different approaches to model communication and cooperation. The approaches are team automata, a well-defined variant of communicating automata, and statecharts, heavily used in object-oriented modelling methods. The comparison yields interesting insights for modelling communication and cooperation. In particular, the differences between action-based, synchronous and state-based, asynchronous communication are elucidated.

Multimedia in der Informatik-Lehre - Engels, Gregor; Doberkat, Ernst-Erich (Informatik bewegt. 32. Jahrestagung der Gesellschaft für Informatik, 2002, Lecture Notes in Informatics)
Neue Medien werden in der universitären Lehre in zunehmendem Maße eingesetzt. Nachdem sich noch vor einigen Jahren nur vereinzelte Pilotprojekte mit dem Thema beschäftigt haben, wird inzwischen eine Vielzahl von Projekten öffentlich gefördert. Als Beispiel sei das BMBF-Förderprogramm Neue Medien in der Hochschullehre genannt. In der Informatik haben nicht zuletzt die hohen Studierendenzahlen dazu beigetragen, multimediale Elemente in der Lehre als ein mögliches Mittel zur Bewältigung der hohen Lehrbelastung bei gleichzeitiger Wahrung von Qualität und Vielfalt der Lehre anzusehen. Das fachliche Interesse vieler Informatiker am Thema Multimedia kommt hinzu. Im Workshop Multimedia in der Informatik-Lehre wird ein Überblick über gegenwärtige Ansätze zur Unterstützung der Lehre in der Informatik mit multimedialen Mitteln gegeben und es werden Erfahrungen und Konsequenzen diskutiert.

High-Level Net Processes - Ehrig, Hartmut; Hoffmann, Kathrin; Padberg, Julia; Baldan, Paolo; Heckel, Reiko (Formal and Natural Computing: Essays Dedicated to Grzegorz Rozenberg)
The notion of processes for low-level Petri nets based on occurrence nets is well known and it represents the basis for the study of the non-sequential behavior of Petri nets. Processes for high-level nets N are often defined as processes of the low level net Flat(N) which is obtained from N via a construction called flattening. In this paper we define high-level processes for high-level nets based on a suitable notion of high-level occurrence nets. The flattening of a high-level occurrence net is in general not a low-level occurrence net, due to so called assignment conflicts in the high-level net. The main technical result is a syntactical characterization of assignment conflicts. But the main focus of this paper is a conceptual discussion of future perspectives of high-level net processes including concurrency and data type aspects. Specifically, in the second part of the paper, we discuss possible extensions of high-level net processes, which are formally introduced for algebraic high-level nets in the first part of this paper. Of special interest are high-level processes with data type behavior, amalgamation, and other kinds of constructions, which are essential aspects for a proposed component concept for high-level nets.

Towards Team-Automata-Driven Object-Oriented Collaborative Work - Engels, Gregor; Groenewegen, Luuk (Formal and Natural Computing: Essays Dedicated to Grzegorz Rozenberg)
The paper studies and compares two different approaches to model communication and cooperation. The approaches are team automata, a well-defined variant of communicating automata, and statecharts, heavily used in object-oriented modelling methods. The comparison yields interesting insights for modelling communication and cooperation. In particular, the differences between action-based, synchronous and state-based, asynchronous communication are elucidated.

Multimedia in der Informatik-Lehre - Engels, Gregor; Doberkat, Ernst-Erich (Informatik bewegt. 32. Jahrestagung der Gesellschaft für Informatik, 2002, Lecture Notes in Informatics)
Neue Medien werden in der universitären Lehre in zunehmendem Maße eingesetzt. Nachdem sich noch vor einigen Jahren nur vereinzelte Pilotprojekte mit dem Thema beschäftigt haben, wird inzwischen eine Vielzahl von Projekten öffentlich gefördert. Als Beispiel sei das BMBF-Förderprogramm Neue Medien in der Hochschullehre genannt. In der Informatik haben nicht zuletzt die hohen Studierendenzahlen dazu beigetragen, multimediale Elemente in der Lehre als ein mögliches Mittel zur Bewältigung der hohen Lehrbelastung bei gleichzeitiger Wahrung von Qualität und Vielfalt der Lehre anzusehen. Das fachliche Interesse vieler Informatiker am Thema Multimedia kommt hinzu. Im Workshop Multimedia in der Informatik-Lehre wird ein Überblick über gegenwärtige Ansätze zur Unterstützung der Lehre in der Informatik mit multimedialen Mitteln gegeben und es werden Erfahrungen und Konsequenzen diskutiert.

Local two-dimensional electron gas formation in p-doped GaAs/InyGa1 yAs/AlxGa1 xAs heterostructures by focused Si-implantation doping - Reuter, D; Meier, Cedrik; Riedesel, C; Wieck, A D (Semiconductor Science and Technology)

Planar Hall sensors for micro-Hall magnetometry - Rahm, M.; Raabe, J.; Pulwey, R.; Biberger, J.; Wegscheider, W.; Weiss, D.; Meier, Cedrik (Journal of Applied Physics)

Towards a Formal Framework for Inter-Enterprise Application Integration - Heckel, Reiko; Engels, Gregor (Proceedings of the Closing Workshop of the TMR Network GETGRATS (2002), Bordeaux (France))
A major concern of software development today is the integration of applications of different enterprises, e.g., over the internet. This requires a shift of focus from system development towards integration of enterprise models and evolution of systems. We propose a conceptual framework for a method addressing these issues and discuss its formalization by means of graph transformation concepts.

Process-Oriented, Flexible Composition of Web Services with UML - Thöne, Sebastian; Depke, Ralph; Engels, Gregor (Proceedings of the International Workshop on Conceptual Modeling Approaches for e-Business: A Web Service Perspective (eCOMO 2002), Tampere (Finland))
The composition of elementary web services to larger-scale services has become an important means to enhance e-business collaborations. If such composite web services can also integrate legacy components that are not yet provided as web services, the number of possible compositions is increased. Following a process-oriented approach, the compositions can be described as control- and data-flow between available web services and components. This paper discusses the Business Process Execution Language for Web Services (BPEL4WS), an existing service composition language, and proposes UML-WSC as an alternative, visual language. For the advanced description of service interfaces, UML-WSC extends the type system of the established Web Service Definition Language (WSDL).

Towards Consistency-Preserving Model Evolution - Engels, Gregor; Küster, Jochen; Heckel, Reiko (Proceedings of the International Workshop on Principles of Software Evolution(satellite event of the ICSE 02), Orlando, Florida (USA))

Towards Graph Transformation with Time - Gyapay, Szilvia; Heckel, Reiko (Proceedings of the APPLIGRAPH Workshop on Application of Graph Transformation (AGT 2002, satellite event of the ETAPS 2002), Grenoble (France))

Towards Automatic Translation of UML Models into Semantic Domains - Heckel, Reiko; Küster, Jochen; Taentzer, Gabriele (Proceedings of the APPLIGRAPH Workshop on Applied Graph Transformation (AGT 2002, satellite event of the ETAPS 2002), Grenoble (France))
The use of UML for software specification leads usually to lots of diagrams showing different aspects and components of the software system in several views. In order to support a view-oriented approach to system modeling, consistency views and in between views has to be manageable. It is a reasonable approach to consistency management when first chossing a suitable semantic domain, provide a partial mapping into this domain, and specity as well as verify consistency constraints formulated in that domain. Annotated meta model rules can be used to translate elements of UML models into the semantic domain chosen. In this contribution, we consider triple graph grammars and attributed graph transformation approaches for the precise definition of meta model rules an outline the tool support for automatic translation.

Extended Model Relations with Graphical Consistency Conditions - Hendrik Hausmann, Jan; Heckel, Reiko; Sauer, Stefan (Proceeding of the Workshop on Consistency Problems in UML-based Software Development (satellite event of the UML 2002), Dresden (Germany))
Consistency of models and model transformations are strongly interrelated topics. It is thus desirable to have a single notation to express model properties concerning both aspects. When using meta modeling techniques, graph transformations are a natural candidate to express model transformations. This paper explores the use of graph transformations for denoting consistency conditions between models. This technique yields benefits for different types of interrelation between transformation and consistency. A special focus is put on the generation of automatic consistency-establishing transformations.

Towards a Standard Interface for Runtime Inspection in AOP Environments - Mehner, Katharina; Rashid, Awais (Proceedings Workshop on Tools for Aspect-Oriented Software Developement (satellite event of the OOPSLA 2002), Seattle, WA (USA))

Lightweight Modeling of Dynamic Websites using UML - Schattkowsky, Tim; Lohmann, Marc; Heckel, Reiko (Proceedings of Workshop on Web Engineering (satellite event of the ICSE 2002), Orlando, FL (USA))
Development of small- or medium scale Web applications is usually performed by teams consisting of graphic designers responsible for the layout and software developers realizing the business logic. Due to short production cycles, these people have to work in parallel on the implementation. Because of the different backgrounds of the people involved and the relative simplicity of the application, a simple design process and modeling approach is required which supports communication between team members and helps to identify and relate their respective tasks. We propose a simple subset of the UML adapted to the problem domain by means of stereotypes. Based on the design, we propose a strategy for generating code templates specifically tailored to the tasks of each team member, so that the implementation can immediately start in parallel when the modeling is complete.

Planspiel zur Messebeteiligung "Marmelade" - Materialband mit CD-ROM - Kennerknecht, M.; Kremer, H.-Hugo; Sloane, Peter F. E.

QoS-Conditionalized Handoff for Mobile IPv6 - Fu, Xiaoming; Karl, Holger; Kappler, Cornelia (NETWORKING 2002, Networking Technologies, Services, and Protocols; Performance of Computer and Communication Networks; and Mobile and Wireless Communications, Second International IFIP-TC6 Networking Conference, Pisa, Italy, May 19-24, 2002, Proceedings)

A protocol extension to HiperLAN/2 to support single-relay networks - Hollos, Daniel; Karl, Holger (Mobile Ad-Hoc Netzwerke, 1. deutscher Workshop über Mobile Ad-Hoc Netzwerke WMAN 2002, 25.-26. März 2002 in Ulm)

Control of the confining potential in ballistic constrictions using a persistent charging effect - Fischer, S. F.; Apetrii, G.; Skaberna, S.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Flux-quantum-modulated Kondo conductance in a multielectron quantum dot - Fühner, C.; Keyser, U. F.; Haug, R. J.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Quantum wire fabrication from compensating-layer GaAs–AlGaAs heterostructures - Kähler, D.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Microelectronic Engineering)

Aharonov–Bohm cages in the GaAlAs/GaAs system - Naud, C.; Faini, G.; Mailly, D.; Vidal, J.; Douçot, B.; Montambaux, G.; Wieck, A.; Reuter, Dirk (Physica E: Low-dimensional Systems and Nanostructures)

Anomalous In-Plane Motion of Excitons in Single GaAs Quantum Wells - Pulizzi, F.; Christianen, P.C.M.; Maan, J.C.; Eshlaghi, S.; Reuter, Dirk; Wieck, A.D. (physica status solidi (a))

Fabrication of quantum point contacts by engraving GaAs/AlGaAs heterostructures with a diamond tip - Regul, J.; Keyser, U. F.; Paesler, M.; Hohls, F.; Zeitler, U.; Haug, R. J.; Malavé, A.; Oesterschulze, E.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Fabrication of two-dimensional in-plane gate transistors by focused ion beam doping - Reuter, Dirk; Meier, Cedrik; Seekamp, A; Wieck, A.D (Physica E: Low-dimensional Systems and Nanostructures)

Growth of InAs quantum dots on focussed ion beam implanted GaAs(100) - Reuter, Dirk; Schafmeister, P; Koch, J; Schmidt, K; Wieck, A.D (Materials Science and Engineering: B)

A multipurpose torsional magnetometer with optical detection - Schaapman, M. R.; Christianen, P. C. M.; Maan, J. C.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electronic structure of InAs self-assembled quantum dots - Schmidt, K.H.; Bock, C.; Kunze, U.; Khorenko, V.V.; Malzer, S.; Döhler, G.H.; Versen, M.; Reuter, Dirk; Wieck, A.D. (Materials Science and Engineering: B)

Phonon excitation of a two-dimensional electron system around ν=1 - Schulze-Wischeler, F.; Zeitler, U.; Hohls, F.; Haug, R.J.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Quantum dot micro-LEDs for the study of few-dot electroluminescence, fabricated by focussed ion beam - Vitzethum, M.; Schmidt, R.; Kiesel, P.; Schafmeister, P.; Reuter, Dirk; Wieck, A.D.; Döhler, G.H. (Physica E: Low-dimensional Systems and Nanostructures)

A novel photoconductive detector for single photon detection - Vitzethum, M.; Schmidt, R.; Kiesel, P.; Schafmeister, P.; Koch, J.; Reuter, Dirk; Wieck, A.D.; Döhler, G.H. (Physica E: Low-dimensional Systems and Nanostructures)

Single-Electron Tunneling through Individual InAs Quantum Dots within a Saddle Point Potential - Versen, M.; Schmidt, K.H.; Bock, C.; Reuter, Dirk; Wieck, A.D.; Kunze, U. (physica status solidi (b))

Increased thermal budget for selectively doped heterostructures by employing AlAs/GaAs superlattices - Reuter, Dirk; Meier, C.; Álvarez, M. A. Serrano; Wieck, A. D. (Applied Physics Letters)

Layer-compensated selectively doped AlxGa1-xAs/GaAs heterostructures as a base material for nanolithography - Reuter, Dirk; Kähler, D; Kunze, U; Wieck, A D (Semiconductor Science and Technology)

Increased mobility anisotropy in selectively doped AlxGa1−xAs/GaAs heterostructures with high electron densities - Reuter, Dirk; Versen, M.; Schneider, M. D.; Wieck, A. D. (Journal of Applied Physics)

Layer-compensated selectively doped AlxGa1-xAs/GaAs heterostructures as a base material for nanolithography - Reuter, Dirk; Kähler, D; Kunze, U; Wieck, A D (Semiconductor Science and Technology)

Hot-Electron Effects in Two-Dimensional Hopping with a Large Localization Length - Gershenson, M. E.; Khavin, Yu. B.; Reuter, Dirk; Schafmeister, P.; Wieck, A. D. (Physical Review Letters)

Nanoscale devices fabricated by direct machining of GaAs with an atomic force microscope - Versen, M; Klehn, B; Kunze, U; Reuter, Dirk; Wieck, A.D (Ultramicroscopy)

Fabrication of a quantum point contact by the dynamic plowing technique and wet-chemical etching - Skaberna, S; Versen, M; Klehn, B; Kunze, U; Reuter, Dirk; D. Wieck, A (Ultramicroscopy)

In-plane and perpendicular tunneling through InAs quantum dots - Schmidt, K.H; Versen, M; Bock, C; Kunze, U; Reuter, Dirk; Wieck, A.D (Physica E: Low-dimensional Systems and Nanostructures)

Electron transport through a single InAs quantum dot - Schmidt, K. H.; Versen, M.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Dependence of the longitudinal resistance on edge potential and electron density in quantum Hall systems - Heidtkamp, Christian; Lassen, Sabine; Schneider, Marcus; Reuter, Dirk; Versen, Martin; Wieck, Andreas D. (Physica B: Condensed Matter)

A compact electron beam evaporator for carbon doping in solid source molecular beam epitaxy - Reuter, Dirk; Wieck, A. D.; Fischer, A. (Review of Scientific Instruments)

A compact electron beam evaporator for carbon doping in solid source molecular beam epitaxy - Reuter, Dirk; Wieck, A. D.; Fischer, A. (Review of Scientific Instruments)

Mechanical stress and magnetism of ferromagnetic monolayers - Sander, D; Enders, A; Schmidthals, C; Reuter, Dirk; Kirschner, J (Surface Science)

Stranski-Krastanov layers of Fe on W(1 1 0): A combined MOKE, LEED, SAM and stress measurement investigation - Sander, D.; Enders, A.; Schmidthals, C.; Reuter, Dirk; Kirschner, J. (Journal of Magnetism and Magnetic Materials)

The correlation between mechanical stress and magnetic properties of ultrathin films - Sander, D; Skomski, R; Enders, A; Schmidthals, C; Reuter, Dirk; Kirschner, J (Journal of Physics D: Applied Physics)

Anisotropic diffusion of3dmetals on W(110): Competition between crystalline structure and surface steps - Reuter, Dirk; Gerth, G.; Kirschner, J. (Physical Review B)

Formation of copper crystallites on a Cu/Fe/Cu(100) sandwich - Wiessner, A.; Agne, M.; Reuter, Dirk; Kirschner, J. (Surface Science)

Modifying diffusion anisotropies: Cap layer induced changes in spreading anisotropies - Reuter, Dirk; Gerth, G.; Kirschner, J. (Journal of Applied Physics)

Good/Bad Girls and their Fathers - Tönnies, Merle (Journal for the Study of British Cultures)

Laughter in Nineteenth-Century British Theatre: From Genial Blending to Harsh Distinctions - Tönnies, Merle (Internationale Forschungen zur Allgemeinen und Vergleichenden Literaturwissenschaft)

The 'Sensationalist Theatre of Cruelty' in 1990s Britain, its 1960s Forebears and the Beginning of the 21st Century - Tönnies, Merle (Contemporary Drama in English)

Betriebsprojekttage – Lernortkooperation im Gewerk Friseur/in: Projektaufgaben im Pflegebereich und Überlegungen zu deren Einsatzmöglichkeiten in Berufsbildenden Schulen - Beutner, Marc (Aktuelle arbeits-, berufs- und bildungsbezogene Herausforderungen an das Berufsfeld Körperpflege in der Dienstleistungs- und Wissenschaftsgesellschaft)

Ausbildungsbereitschaft in Klein- und Mittelunternehmen – Ausgewählte Ergebnisse einer Längsschnittuntersuchung 1999 und 2000 - Beutner, Marc (Berufsbildung im Handwerk: Kontinuität und Perspektiven)

Qualität der Ausbildung in der europäischen Union: Ergebnisse aus einer Vergleichsstudie - Beutner, Marc; Fischer, A (Berufsbildung im Handwerk: Kontinuität und Perspektiven)

Voigts-Virchow, E. (Hg.): Mediated Drama. Dramatized Media, 2000 - Tönnies, Merle (Forum Modernes Theater)

M-SCTP: Design and prototypical implementation of an end-to-end mobility concept - Xing, Wei; Karl, Holger; Wolisz, Adam; Müller, Harald (In Proc. 5th Intl. Workshop The Internet Challenge: Technology and Applications)

Sluggish Consumers: An Evolutionary Solution to the Bertrand Paradox - Hehenkamp, Burkhard (Games and Economic Behavior)

Light Propagation- and Many-particle-induced Non-Lorentzian Lineshapes in Semiconductor Nanooptics - Förstner, Jens; Ahn, K.J.; Danckwerts, J.; Schaarschmidt, M.; Waldmüller, I.; Weber, C.; Knorr, A. (physica status solidi (b))
The occurrence of non-Lorentzian lineshapes is analyzed for a variety of nanooptical semiconductor systems such as quantum wells and quantum dots. Their origin is traced back to light–matter interaction (light propagation) and many-particle correlations (electron–electron and electron– phonon interaction).
Keywords: tet_topic_polariton

Theory of ultrafast dynamics and lineshape of semiconductor quantum well intersubband emitters - Waldmüller, Ines; Förstner, Jens; Knorr, Andreas (Nonlinear Optics: Materials, Fundamentals and Applications)
On the basis of a density matrix approach including electron-electron scattering, a detailed analysis of the temporal dynamics and the dephasing process after optical excitation in intersubband emitters is presented for a wide range of parameters.
Keywords: tet_topic_qw

Coherent nonlinear pulse propagation on a free-exciton resonance in a semiconductor - Nielsen, N. C.; Linden, S.; Kuhl, J.; Förstner, Jens; Knorr, A.; Koch, S. W.; Giessen, H. (Physical Review B)
The coherent exciton-light coupling in pulse propagation experiments on the A-exciton resonance in bulk CdSe is investigated over a broad intensity range. At low light intensities, polariton propagation beats due to interference between excited states on both polariton branches are observed. In an intermediate intensity regime, the temporal polariton beating is suppressed in consequence of exciton-exciton interaction. At the highest light intensities, self-induced transmission and multiple pulse breakup are identified as a signature for carrier density Rabi flopping. Exciton-phonon scattering is shown to gradually eliminate coherent nonlinear propagation effects due to enhanced dephasing of the excitonic polarization. Calculations using the semiconductor Maxwell-Bloch equations are in qualitative agreement with the experimental data.
Keywords: tet_topic_polariton

Nonlinear Pulse Propagation in Semiconductors: Hole Burning within a Homogeneous Line - Förstner, Jens; Knorr, A.; Koch, S. W. (Physical Review Letters)
Features reminiscent of spectral hole burning in a homogeneous line are predicted to result from the interaction of small area pulses with the semiconductor exciton resonance. The small area pulses may be designed through pulse shaping or evolve naturally in bulk semiconductors via polaritonic effects. The spectral features exhibit signatures that are characteristic for the underlying material nonlinearity and should occur in any system with isolated spectral resonances and coherent nonlinearities.
Keywords: tet_topic_polariton

Nonlinear Polariton Pulse Propagation in Bulk Semiconductors - Förstner, Jens; Knorr, A.; Kuckenburg, S.; Meier, T.; Koch, S.W.; Giessen, H.; Linden, S.; Kuhl, J. (physica status solidi (b))
Nonlinear propagation of optical pulses through an extended bulk semiconductor is investigated using the coupled semiconductor Maxwell‐Bloch equations including excitation induced correlations. For short pulse excitation around the exciton resonance, the theory describes the development of polariton beats and their suppression at increasing input pulse intensities due to the coupling of single exciton states to the Coulomb‐correlated continuum of two‐exciton states. A comparison of the theoretical results with experimental observations for CdSe bulk material is presented.
Keywords: tet_topic_polariton

Outsourcing und Professionalisierung in der Personalarbeit: Eine transaktionskostentheoretisch orientierte Studie - Matiaske, W; Kabst, Rüdiger (Zeitschrift für Personalforschung, Sonderband 'Neue Formen der Beschäftigung und Personalpolitik')

Data Warehouse in der Marktforschung - Analyse von Benutzeraktivitäten in virtuellen Welten - Schryen, Guido; Schoenen, Markus (Data Warehousing 2002)
Bei der Online-Marktforschung lässt sich mit Hilfe virtueller 3D-Welten das Konsumentenverhalten beobachten. Da die Struktur der dabei anfallenden Daten multidimensional ist und die marktforschungsrelevanten Anfragen eine hohe OLAP-Affinität aufweisen, wurde hierzu im Rahmen des Forschungsprojekts Benevit ein Data Warehouse konzipiert und realisiert. Im Rahmen einer Standardisierung der Protokollierung von Konsumentenaktivitäten und deren prototypischen Realisierung erwies sich der Data Warehouse/OLAP-Ansatz zur Speicherung, Analyse und Präsentation der Marktforschungsdaten als adäquates Instrumentenbündel.

Elektronisches Papier - Display-Technologie mit weitem Anwendungsspektrum - Schryen, Guido; Karla, Jürgen (Wirtschaftsinformatik)
Mit dem elektronischen Papier wird in der Displayforschung ein neuer materialtechnologischer Ansatz verfolgt: Elektronisches Papier besteht aus einer dünnen, flexiblen Folie, in der farbige Pigmente mittels elektrischer Felder ausgerichtet werden. Die Vorteile gegenüber traditionellen Technologien wie beispielsweise LCD-Displays bestehen zum einen in niedrigeren Herstellungskosten (niedrigere Produktionskosten und geringere Materialkosten) und einem geringeren Gewicht. Zum anderen entsteht eine bessere Lesbarkeit, da sich Reflexion, Kontrast und mögliche Betrachtungswinkel verbessern bzw. vergrößern. Diese Potenziale können bei Anzeigetafeln, Computerdisplays und mobilen Endgeräten ausgeschöpft werden. Mit der Eigenschaft, fast beliebige Materialien als Trägermedium zu verwenden, öffnet sich auch die Anwendungsmöglichkeit des biegsamen, elektronischen Mediums für Zeitungen und Zeitschriften. Die US-Unternehmen E Ink und Gyricon Media bieten eine zunehmend größere Produktpalette mit elektronischem Papier an.
Keywords: Elektronisches Papier; Elektronische Tinte; E Ink; Gyricon Media; Displays; Mobile Endger{\

Elektronische Zeitung - das Erbe Gutenbergs? - Schryen, Guido (i-com. Zeitschrift für interaktive und kooperative Medien)

Data Management in Networks: Experimental Evaluation of a Provably Good Strategy - Krick, Christof; Meyer auf der Heide, Friedhelm; Räcke, Harald; Vöcking, Bernhard; Westermann, Matthias' (Theory of Computing Systems)

The randomized sample tree: a data structure for interactive walkthroughs in externally stored virtual environments - Klein, Jan; Krokowski, Jens; Fischer, Matthias; Wand, Michael; Wanka, Rolf; Meyer auf der Heide, Friedhelm (Proceedings of the ACM symposium on Virtual reality software and technology - VRST '02)
We present a new data structure for rendering highly complex virtual environments of arbitrary topology. The special feature of our approach is that it allows an interactive navigation in very large scenes (30 GB/400 million polygons in our benchmark scenes) that cannot be stored in main memory, but only on a local or remote hard disk. Furthermore, it allows interactive rendering of substantially more complex scenes by instantiating objects. For the computation of an approximate image of the scene, a sampling technique is used. In the preprocessing, a so-called sample tree is built whose nodes contain randomly selected polygons from the scene. This tree only uses space that is linear in the number of polygons. In order to produce an image of the scene, the tree is traversed and polygons stored in the visited nodes are rendered. During the interactive walkthrough, parts of the sample tree are loaded from local or remote hard disk. We implemented our algorithm in a prototypical walkthrough system. Analysis and experiments show that the quality of our images is comparable to images computed by the conventional z-buffer algorithm regardless of the scene topology.

Energy, congestion and dilation in radio networks - Meyer auf der Heide, Friedhelm; Schindelhauer, Christian; Volbert, Klaus; Grünewald, Matthias (Proceedings of the fourteenth annual ACM symposium on Parallel algorithms and architectures - SPAA '02)

Set Oriented Numerical Methods for Dynamical Systems - Dellnitz, Michael; Junge, Oliver (Handbook of Dynamical Systems)

Finding zeros by multilevel subdivision techniques - Dellnitz, M. (IMA Journal of Numerical Analysis)